STUDENTS’ PERCEPTION TOWARDS INTERPROFESSIONAL EDUCATION (IPE) USING TEAM-BASED LEARNING (TBL) - Warjidin Aliyanto; Retno Puji Hastuti; Dwita Oktaria (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: The healthcare system consists of collaborations from multiple related professions to provide superior services for patients. The ability to cooperate in an interprofessional environment should be introduced at an early stage for healthcare students in the workplace amongst various disciplines. Interprofessional education (IPE), is an innovation where a group of students from several health professions conduct learning together, to create effective collaboration in order to improve the quality of health services. One of the active learning methods that can be used is Team-Based Learning (TBL). This study aims to elaborate students' perception of IPE learning using TBL as the active learning method.Method: The mixed – method is applied in this research. 162 students from four applied undergraduate study programs at the Tanjungkarang Health Polytechnic are sampled. 26 groups consisting of 6 - 7 students from various study programs are divided from the sample. Data was collected using sli.do at the end of TBL session.Results: Student perceptions included: entertaining learning processes, higher knowledge absorptions, improved interprofessional teamwork and communication and better critical thinking skills. Refining teacher competency, increasing profession diversity in the discussions, increasing session duration and higher topic complexity are important factors to ameliorate further IPE learning using TBL. 81% of students had a positive (excellent and good) response in regards to IPE learning using the TBL.Conclusion: Students possess a positive perception and increased benefits for IPE learning using TBL. TBL may be one of the prospective methods to convey IPE concepts.